Chk1 phosphorylated at serine345 is a predictor of early local recurrence and radio‐resistance in breast cancer. Issue 2 (3rd October 2015) - Alsubhi, Nouf; Middleton, Fiona; Abdel-Fatah, Tarek M.A.; Stephens, Peter; Doherty, Rachel; Arora, Arvind; Moseley, Paul M.; Chan, Stephen Y.T.; Aleskandarany, Mohammed A.; Green, Andrew R.; Rakha, Emad A.; Ellis, Ian O.; et al.
Abstract : Radiation‐induced DNA damage activates the DNA damage response (DDR). DDR up‐regulation may predict radio‐resistance and increase the risk of early local recurrence despite radiotherapy in early stage breast cancers. In 1755 early stage breast cancers, DDR signalling [ATM, ATR, total Ckh1, Chk1 phosphorylated at serine345 (pChk1), Chk2, p53], base excision repair [PARP1, POLβ, XRCC1, FEN1, SMUG1], non‐homologous end joining (Ku70/Ku80, DNA‐PKcs) and homologous recombination [RAD51, BRCA1, γH2AX, BLM, WRN, RECQL5, PTEN] protein expression was correlated to time to early local recurrence. Pre‐clinically, radio‐sensitization by inhibition of Chk1 activation by ATR inhibitor (VE‐821) and inhibition of Chk1 (V158411) were investigated in MDA‐MB‐231 (p53 mutant) and MCF‐7 (p53 wild‐type) breast cancer cells. In the whole cohort, 208/1755 patients (11.9%) developed local recurrence of which 126 (61%) developed local recurrence within 5 years of initiation of primary therapy. Of the 20 markers tested, only pChk1 and p53 significantly associated with early local recurrence (p value = 0.015 and 0.010, respectively). When analysed together, high cytoplasmic pChk1‐nuclear pChk1 (p = 0.039), high cytoplasmic pChk1‐p53 (p = 0.004) and high nuclear pChk1‐p53 (p = 0.029) co‐expression remain significantly linked to early local recurrence. In multivariate analysis, cytoplasmic pChk1 level independently predicted early local recurrence (p = 0.025). In patients who received adjuvant local radiotherapy (n = 949), p53 (p = 0.014) and high cytoplasmic pChk1‐p53 (p = 0.017) remain associated with early local recurrence. Pre‐clinically, radio‐sensitisation by VE‐821 or V158411 was observed in both MCF‐7 and MDA‐MB‐231 cells and was more pronounced in MCF‐7 cells. We conclude that pChk1 is a predictive biomarker of radiotherapy resistance and early local recurrence. Highlights: Radiation‐induced DNA damage activates the DNA damage response (DDR). 1755 breast cancers were profiled for DDR and correlated to local recurrence. High p‐Chk1 was significantly associated with local recurrence. ATR‐Chk1 pathway inhibition increased radio sensitivity in breast cancer cells.